Development of new synthesised multilayered bioceramics for dental crown restorations / Ali Abdullah Alwan al-Maqtari - Ali Abdullah, Alwan al-Maqtari (2017)
This study aimed to investigate and establish the biomechanical behaviour of functionally graded dental ceramic cores in simulated models of a maxillary second premolar using 3D finite element analysis. It also aimed to synthesise and evaluate the microstructural, physical, thermal, and mechanical properties of a new multilayered bioceramic cores. The shear bond strength of the synthesised zirconia and alumina ceramic core with/without infiltrated graded silica with their corresponding veneering porcelains were also evaluated. Finally, cytotoxicity effects of the new synthesised dental bioceramic core (powders and discs) were evaluated using human gingival fibroblast (HGF-1) cells. Materials and Methods. An intact maxillary premolar was digitized with a CT scanner. Eight different models (Models A-H) were developed. A total of 243 images were obtained, and the image data was saved as files in DICOM format. Mimics software was used for reconstruction of the data converted to the DICOM file in the 3D FE model on the computer. The 3D FE models were constructed meshed. The models were constrained at the bottom boundaries. A static load (200 N) was applied in three different directions (oblique, horizontal, and vertical) at three different areas on all models. All materials were assumed to be isotropic and homogeneous. The von Mises stress distributions along the veneer-core-cement-dentin interfaces and interface stresses between the crown and its surrounding structures were investigated under oblique, vertical, and horizontal loadings. Also, strain distribution at the veneer-core-cement-dentine interfaces was also investigated. Samples containing 0, 20, 40, and 50 wt.% of Al2O3 particles in the Y-ZrO2 matrix were prepared by uniaxial pressing (200 MPa) and sintered in air at 1500 °C for 2h. The microstructure (FESEM, EDX, XRD), physical (density, porosity, shrinkage), thermal (TMA), and mechanical (Vickers hardness, compressives strength, elastic modulus, and strain) were characterized and analyzed. The shear bond strength was carried out. Subsequently, all specimens were subjected to a shear load in a universal testing machine. Fractured specimens were evaluated microscopically (SEM, EDX) to determine the failure mode. In vitro biocompatability evaluation of synthesised ceramic powders and discs were tested and to determine the cytotoxic level of the synthesised ZrO2–Al2O3 ceramic composites by using the resazurin proliferation assay with HGF-1 cells lines after 72 h. For ceramic discs, ANOVA was used to determine statistical significant differences among the synthesised ceramic disc groups, and also Dunnett’s test was used for multiple comparisons. For powders ceramics, two-way ANOVA was employed to determine the interaction influence between synthesised ceramic powders with five different concentrations. t-test was used to compare the mean between non-sintered and sintered synthesised ceramics. The significant level was set at 0.05. Results and conculsions. The results showed that functionally graded structured dental ceramic cores models, B, C, D, E, F, and G, demonstrated desirable advantages in terms of stress distribution compared to homogenous zirconia (model A) cores. Dental ceramic crowns with bilayered structure cores dissipated the localized and interfacial stress and strain efficiently. Functionally graded material approach can be used to design new dental cores in order to reduce stress concentrations and interfacial stresses successfully in the dental crown. Fully dense ceramic materials were obtained with a Vickers hardness test ranging between 1292.8 VH and 1711.9 VH, depending on the amount of Al2O3 in the ZrO2 matrix. There was no significant influence from the infiltrated of graded silica addition to the shear bond strength. The results indicated that the shear bond strength between zirconia/alumina cores and veneering ceramics was not affected by infiltrated graded silica. Also, the results indicated that powder form ceramic was cytotoxic to HGF-1 cells at higher concentrations. However, at lower concentrations powder ceramics showed minimal toxicity. Disc ceramics showed minimal toxicity on HGF-1 cells.